Do some chemotaxis-growth models possess Lyapunov functionals?. (March 2016) - Horstmann, Dirk
Abstract: In spirit of a result by W. Alt from 1980 we give some sufficient criteria that guarantee the existence of Lyapunov functionals for parabolic cross-diffusion models including chemotaxis-growth models with non-diffusive chemotactic signals (resp. with non-diffusive memory).